Effectiveness of the combat pelvic protection system in the prevention of genital and urinary tract injuries: An observational study. Issue 4 (October 2015) - Oh, John S.; Do, Nhan V.; Clouser, Mary; Galarneau, Michael; Philips, Jennifer; Katschke, Adrian; Clasper, Jon; Kuncir, Eric J.
Abstract : BACKGROUND: Historically, the incidence of genital and urinary tract (GU) injuries in major conflicts has been approximately 5%. To mitigate the risk of blast injury to the external genitalia, the United States and United Kingdom issued protective overgarments and undergarments to troops deployed in support of Operation Enduring Freedom. These two systems combined constitute the pelvic protection system (PPS). Our hypothesis was that PPS use is associated with a reduction of GU injuries in subjects exposed to dismounted improvised explosive device blast injuries. METHODS: We identified two groups for comparison: those who were confirmed to have worn the PPS at time of injury (n = 58) and a historical control group who were confirmed as not wearing the PPS (non-PPS) (n = 61). Patients with any level of lower extremity amputation from dismounted improvised explosive device blast mechanism were included. The primary outcome measure was presence of a GU injury on admission. A univariate analysis assessing the strength of association with odds ratios and 95% confidence intervals was performed between the PPS and non-PPS groups. RESULTS: Mean Injury Severity Score (ISS) was higher in the PPS versus the non-PPS group (26.1 vs. 19.3, p = 0.0012). Overall, 31% of the patients in the PPS group sustained at least one GU injury versus 62.3% in the non-PPS group. The odds ratio of sustaining a GU injury in the PPS group as compared with the PPS group is 0.28 (31% vs. 62.3%; 95 % confidence interval, 0.62–0.12; p < 0.001). The most frequent injures were open scrotal/testes wounds, followed by open penis, and open bladder/urethra injuries. CONCLUSION: The use of the PPS is associated with a decreased odds ratio of GU injury. Despite a 31% absolute reduction, future work should focus on improved efficiency. LEVEL OF EVIDENCE: Prognostic/epidemiologic study, level IV; therapeutic study, level V.